2008
DOI: 10.1158/1055-9965.epi-08-0528
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Extracts for the Prevention of Metachronous Colorectal Adenomas: A Pilot Study

Abstract: Background: Experimental studies indicate the chemopreventive properties of green tea extract (GTE) on colorectal cancer. Epidemiologically, green tea consumption of >10 cups daily reduced colorectal cancer risk in Japanese. Because colorectal adenomas are the precursors to most sporadic colorectal cancers, we conducted a randomized trial to determine the preventive effect of GTE supplements on metachronous colorectal adenomas by raising green tea consumption in the target population from an average of 6 cups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(140 citation statements)
references
References 41 publications
5
131
2
2
Order By: Relevance
“…Does green tea can decrease the CRC risk? Results from a human experimental randomized controlled trail support the hypothesis of a protective role of green tea for the chemoprevention of metachronous colorectal adenomas (Shimizu et al, 2008). Another randomized, placebo controlled, multicentre trial to investigate the effect of green tea extract nutriprevention of metachronous colon adenomas in the elderly population is undergoing (Stingl et al, 2011), whether it can obtain a significant result is still unkown.…”
Section: Discussionmentioning
confidence: 91%
“…Does green tea can decrease the CRC risk? Results from a human experimental randomized controlled trail support the hypothesis of a protective role of green tea for the chemoprevention of metachronous colorectal adenomas (Shimizu et al, 2008). Another randomized, placebo controlled, multicentre trial to investigate the effect of green tea extract nutriprevention of metachronous colon adenomas in the elderly population is undergoing (Stingl et al, 2011), whether it can obtain a significant result is still unkown.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, supplementation with GTCs can significantly prevent the development of both colorectal adenomas and prostate cancers without causing adverse effects (46,47). A double-blind, placebo-controlled pilot study showed that EGCG has the potential to increase fat oxidation in men (48), although more studies with a larger sample size are required to confirm this effect.…”
Section: Gapdhmentioning
confidence: 99%
“…Based on our successful prevention study on the recurrence of colorectal adenomas in Japanese patients as a result of daily consumption of green tea beverage supplemented with tablets of green tea extract containing (−)-epicatechin (EC; ref. 7), we think that the cancer-preventive activity of curcumin could be enhanced using some components of the diet in daily consumption. To achieve this, we first looked at the effects of EC, which is an inert tea catechin (8), without a galloyl group, in the above-mentioned cancer-preventive activities.…”
Section: Introductionmentioning
confidence: 99%